Study guides

☆☆

Q: What is 3x - 11x?

Write your answer...

Submit

Still have questions?

Related questions

-11

14

-3x + 6 + 15x =11x + 8 ie -3x + 15x - 11x = 8 - 6 ie x = 2

3x+5y+8x+2y combine 3x and 8x to get 11x 11x+5y+2y combine 5y and 2y 11x+7y is the answer.

3x - 4 = 73x = 11x = 3.66666...

11x = 8x-6.............. 11x-8x = -6................... 3x= -6 x = -2

11x + 8 = 8x + 20 3x + 8 = 20 3x = 12 x = 4

If you mean: (3x+1) and (2x+3) are factors of 6xsquared+11x+3 then yes they are

8x - 9 = 11x + 12 8x = 11x + 21 -3x = 21 x = -7

Yes and they add up to 11x

23

x=12

3x2 - 11x - 4 = (x-4)(3 x + 1)

6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)

If you mean: 3x squared -11x -20 = 0 Then: x = -5 or x = 4/3

(3x-4)(x+5)

(3x + 1)(x - 4)

(3x+1)(2x+4)

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

20X - 3 + 3X = 11X + 5 - 8 put those like terms together on the left 23X - 3 = 11X + 5 - 8 like terms together on the right 23X - 3 = 11X - 3 this equation admits of no solution, so is not true X would = 0

no, 4x-3y=11x 3x-5y doesn't equal -11

3x-7 = 14x-29 29-7 = 14x-3x 22 = 11x x = 2 Hope that helps!!;)

8x - 5 + 3x + 17 = 155% 11x + 12 = 1.55 11x = 1.55 - 12 = -10.45 x = - (10.45/11) = - 0.95

-8x + 5 - 3x = -6Combine the 'x' terms on the left side:-11x + 5 = -6Subtract 5 from each side:-11x = -11Divide each side by -11:x = 1

(11x - 2)(3x - 5)

People also asked